2005
DOI: 10.1002/qsar.200430924
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Docking and Design in a Flexible Receptor Site

Abstract: Intrinsic protein flexibility is often ignored in the drug discovery process, however, there is increasing evidence suggesting that many therapeutic targets are flexible. In this work, we describe a method for incorporating receptor flexibility, based on protein side-chain rearrangements, in ligand docking and design. The approach is applied to the docking of a highly potent inhibitor in the acetylcholinesterase binding site and to the generation of ligands in the S1' cavity of human collagenase. Simulations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…In general, protein flexibility is still poorly simulated in many of the available docking packages. Accordingly, most publications on docking and virtual screening on metalloproteases currently concentrate on ensuring [39,41] or improving the accuracy of known ligand binding [151,155,156] and incorporating the protein flexibility into the equation [157], or the use of more pharmacophore-based approaches, such as for ADAM12 [158], Anthrax Lethal Factor [159], and botulinum neurotoxin A metalloprotease [156]. One report [160] of virtual screening-based discovery of novel angiotensinconverting enzyme 2 (ACE2) inhibitors from the NCI library of 140 000 compounds using DOCK 5.1 describes nine compounds chosen from the docking screen for in vitro assay.…”
Section: Metalloproteasesmentioning
confidence: 99%
“…In general, protein flexibility is still poorly simulated in many of the available docking packages. Accordingly, most publications on docking and virtual screening on metalloproteases currently concentrate on ensuring [39,41] or improving the accuracy of known ligand binding [151,155,156] and incorporating the protein flexibility into the equation [157], or the use of more pharmacophore-based approaches, such as for ADAM12 [158], Anthrax Lethal Factor [159], and botulinum neurotoxin A metalloprotease [156]. One report [160] of virtual screening-based discovery of novel angiotensinconverting enzyme 2 (ACE2) inhibitors from the NCI library of 140 000 compounds using DOCK 5.1 describes nine compounds chosen from the docking screen for in vitro assay.…”
Section: Metalloproteasesmentioning
confidence: 99%
“…SkelGen has been adapted to use several static receptors and flexible side chains through its Reflex method [16,17].…”
Section: Receptor Flexibilitymentioning
confidence: 99%
“…It has been demonstrated that incorporating protein structural flexibility is significant for both binding mode predictions and ligand generation [47]. In order to investigate whether the binding process of POM to N1 could be better described by induced-fit theory, we used the module Affinity to implement a flexible docking study on the configuration which had the highest score in the rigid docking.…”
Section: Flexible Affinity Of Pom/na Complexmentioning
confidence: 99%